2017
DOI: 10.1177/0032321716679424
|View full text |Cite
|
Sign up to set email alerts
|

What Citizens Want in Terms of Intra-Party Democracy: Popular Attitudes towards Alternative Candidate Selection Procedures

Abstract: Reforms of intra-party decision-making processes often rest on the idea that citizens want more direct say in these processes, but empirical data to support this claim are scarce. Using original data from the 2014 PartiRep voter survey in Belgium, this article explores the extent to which citizens support alternative intra-party processes. It shows that voters have heterogeneous preferences in terms of candidate selection procedures and that these are not random. ‘Disaffected’ citizens tend to support open pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
1
15
0
2
Order By: Relevance
“…This is particularly the case because the dependent variables analysed here are also consequential in several other areas. For example, Lavezzolo and Ramiro (2017) have shown that these attitudes are central to understand voting for new anti-establishment parties; Close et al (2017) state that they help to understand why citizens prefer different forms of decision making within parties, and Bengtsson and Christensen (2014) argue that they are highly correlated with patterns of political participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly the case because the dependent variables analysed here are also consequential in several other areas. For example, Lavezzolo and Ramiro (2017) have shown that these attitudes are central to understand voting for new anti-establishment parties; Close et al (2017) state that they help to understand why citizens prefer different forms of decision making within parties, and Bengtsson and Christensen (2014) argue that they are highly correlated with patterns of political participation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, right wing ideology amongst Spaniards and Finns shows a significant positive effect upon support for stealth democracy (Bengtsson and Mattila, 2009; Del Río et al, 2016) suggesting that, at least in Europe, ideology is the main factor explaining support for stealth or participatory models as alternatives to existing representative democracy. It is notable that ideology also explains preferences regarding similar issues like intra-party democracy (Close et al, 2017).…”
Section: Explanatory Factors I: Theory and Hypothesesmentioning
confidence: 99%
“…Indeed, the array of organizational preferences spans a spectrum from more expert-led efficiency to growing demands for more direct participation in democratic processes (Bengtsson & Mattila, 2009;Close, Kelbel, & Van Haute, 2017;Font, Wojcieszak, & Navarro, 2015;Webb, 2013). Many conventional political organizations have trouble satisfying preferences for flexible and autonomous engagement that blur distinctions between member-participant and voter-supporter within and beyond electoral politics (Bimber, Flanagin, & Stohl, 2012).…”
Section: The Democratic Interface In the Electoral Arenamentioning
confidence: 99%
“…First, citizens tend to perceive political elites as detached from the rest of the population (Krouwel and Abts, 2007) and they should consequently prefer ‘ordinary’ party members to take crucial decisions over more exclusive actors. Second, this reasoning is supported by empirical research that demonstrates that large parts 4 of the electorate prefer more inclusive selection procedures that involve either party members or even all voters (Close et al, 2017). Based on this reasoning, we argue that citizens should perceive political parties with inclusive leadership as more attractive than parties in which the party elite decides upon leadership.…”
Section: Consequences Of Inclusive Leadership Contestsmentioning
confidence: 93%